Impaired skin regeneration and remodeling after cutaneous injury and chemically induced hyperplasia in taps-transgenic mice - Hildenbrand, Maike; Rhiemeier, Verena Margrit; Hartenstein, Bettina; Lahrmann, Bernd; Grabe, Niels; Angel, Peter; Heß, Jochen (The journal of investigative dermatology, 2010)
Recently, we identified an AP-1-dependent target gene in 12-O-tetradecanoylphorbol-13-acetate (TPA)-treated mouse back skin, which encodes a retroviral-like aspartic proteinase (Taps/Asprv1). Taps expression was detected almost exclusively in stratified epithelia of mouse embryos and adult tissues, and enhanced protein levels were present in several non-neoplastic human skin disorders, implicating a crucial role for differentiation and homeostasis of multilayered epithelia. Here, we generated a mouse model in which Taps transgene expression is under the control of the human ubiquitin C promoter (UBC-Taps). Although no obvious phenotype was observed in normal skin development and homeostasis, these mice showed a significant delay in cutaneous wound closure compared with control animals. Shortly after re-epithelialization, we found an increase in keratinocytes in the stratum granulosum, which express Filaggrin, a late differentiation marker. A hypergranulosum-like phenotype with increased numbers of Filaggrin-positive keratinocytes was also observed in UBC-Taps mice after administration of TPA. In summary, these data show that aberrant Taps expression causes impaired skin regeneration and skin remodeling after cutaneous injury and chemically induced hyperplasia.